Incidence of type 2 diabetes in the elderly in Central Spain: Association with socioeconomic status, educational level, and other risk factors. Issue 2 (April 2022) - Hawkins Carranza, Federico; Corbatón-Anchuelo, Arturo; Bermejo Pareja, Félix; Martín-Arriscado Arroba, Cristina; Vega-Quiroga, Saturio; Benito-León, Julián; Serrano-Ríos, Manuel
Highlights: T2D incidence was 9.8/1000 person-years in a population aged >65 years of Central Spain. T2D incidence was higher in Communities with lower SES. Differences in Educational attainment level contribute to disparities in the development of T2D. This is the first report in an older population of Central Spain of the association of lower Educational levels and the incidence of T2D that may be mediated by BMI. Our study supports that Community differences in SES and education level are critical for public health in the elderly with T2D. Abstract: Aims: To analyze the incidence of type 2 diabetes (T2D) in Central Spain and its association with the socioeconomic status (SES), educational level, and other risk factors (RF) in the elderly population of three communities. Methods: Data for 5278 elderly participants (≥65 years old) were obtained using a census population-based survey. There was a first and a second survey three years later. The association between SES, educational level, RF, and T2D incidence was analyzed. Results: The incidence rate for T2D was 9.8/1000 person-years without gender differences. Incident T2D was associated with low SES and lower educational levels. Baseline and follow-up BMI were also the main RFs for T2D. Communities' incidence rates were: (1) Margarita, working-class area: 11.3/1000 person-years; (2) Arévalo, agricultural region: 10.1/1000 person-years and; (3) Lista, professional high-income class area: 7.6/1000 person-years. Conclusion: We found an incidence rate of 9.8/1000 person-years of T2D in the elderly population. The risk of T2D was associated with a lower income and educational level. An increase in BMI may mediate this association. Our results emphasize the necessity of strategies for the prevention of diabetes that includes an approach to SES, educational levels, and other RF among older individuals in Spanish community settings.